La socialisation au féminisme des étudiant·es par les médias après #MeToo - Albenga, Viviane (Politiques de communication, 2021)
La socialisation au féminisme par les médias est un sujet dont l’acuité se renforce depuis le hashtag MeToo. Dans ce contexte, nous montrerons comment certains médias ont pu participer à la socialisation politique au féminisme d’étudiant·es. En replaçant ces effets socialisateurs par rapport aux socialisations familiales et nationales et à l’expérience des violences sexistes, l’article met en évidence que certains médias ont pu agir comme un processus de transformation de dispositions incorporées en dispositions politique. Nous analyserons ensuite les usages politiques de médias en termes de participation et d’information : d’une part, les usages des comptes Instagram féministes ; d’autre part, les effets de la combinaison d’informations politiques généralistes par les réseaux sociaux et Internet aussi bien que la radio et la télévision. Ce dernier usage diversifié est le fait d’étudiant·es avec un capital culturel plus élevé qui se réfèrent davantage à l’histoire du mouvement féministe et de sa production théorique.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; cours; cyberféminisme; discipline; europe; france; féminisme pop; militance; pol4102; premier cycle; périodes historiques; régions géographiques; réseaux sociaux; sciences humaines; socialisation; sociologie; thématiques

Dénoncer les féminicides des femmes autochtones aux États-Unis et au Canada La bande dessinée Deer Woman d’Elizabeth LaPensée, une super-héroïne autochtone éco-féministe ? - Bonadè, Sophie; Hamus-Vallée, Réjane; Journée-Duez, Aurélie (Genre en séries, 2019)
À travers l’analyse de la bande dessinée Deer Woman créée en 2015 par Elizabeth LaPensée (Anishinaabe, Canada), notre article a pour objectif principal d’interroger la notion de « super-héroïne » à l’aune de représentations autochtones engagées. Il s’agit de voir en quoi cette revitalisation du mythe traditionnel de la Femme Cerf (Deer Woman) interroge l’identité en termes de sexe et de genre, la culture et la place des femmes autochtones, en prenant une position radicale face au problème sociétal des féminicides en Amérique du Nord. Nous postulons que la figure de Deer Woman peut aussi être vue aujourd’hui comme une allégorie mettant en garde contre la domination masculine sur les femmes et sur toutes autres formes de vie. Tout d’abord, nous étudierons les caractéristiques formelles de Deer Woman et les mythes fondateurs autochtones qui en sont à l’origine. Nous montrerons ensuite en quoi cette super-héroïne dont les pouvoirs apparaissent après qu’elle a été sexuellement agressée, tend à dénoncer et lutter contre les féminicides touchant les femmes autochtones. Enfin, nous nous demanderons comment cette bande dessinée pourrait laisser entrevoir l’émergence d’une super-héroïne autochtone éco-féministe.
Keywords: amérique du nord; amériques; approches et analyses; arts; bande-dessinée; cours; discipline; environnement; féminicide; féminisme autochtone; féminisme pop; histoire et politique; justice sociale; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; super-héroïnes; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Anti-porn: the resurgence of anti-pornography feminism - Long, Julia (Zed Books, 2012)
"Anti-porn feminism is back. Countering the ongoing 'pornification' of Western culture and society, with lads' mags on the middle shelf and lap-dancing clubs in residential areas, anti-porn movements are re-emerging among a new generation of feminist activists worldwide. This essential new guide to the problems with porn starts with a history of modern pro and anti political stances before examining the ways in which the new arguments and campaigns around pornography are articulated, deployed and received. Drawing on original ethnographic research, it provides an in-depth analysis of the groups campaigning against the pornography industry today, as well as some eye-opening facts about the damage porn can do to women and society as a whole. This unique and inspiring book explains the powerful comeback of anti-porn feminism, and it controversially challenges liberal perspectives and the mainstreaming of a porn culture that threatens to change the very nature of our intimate relationships"–Résumé de l'éditeur.
Section: 246 p. ; 23 cm
Keywords: approches et analyses; corps; cours; discipline; féminisme anti-porn; féminisme pop; militance; patriarcat; premier cycle; sex1911; sexualité; systèmes d'oppressions; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Catching a wave: reclaiming feminism for the 21st century - Dicker, Rory Cooke; Piepmeier, Alison (Northeastern University Press, 2003)
Young women today have benefited from the strides made by grassroots social activists in the 1960s and 1970s, yet they are hesitant to identify themselves as feminists and seem apathetic about carrying the torch of older generations to redress persistent sexism and gender-based barriers. Contesting the notion that we are in a post-feminist age, this collection of essays identifies a third wave of feminism. The contributors argue that the next generation needs to develop a politicized, collective feminism that both builds on the strategies of second wave feminists and is grounded in the material realities and culture of the 21st century. Organized into five sections which mirror the stages of consciousness-raising, the book looks at a broad range of perspectives on the diversity, complexity, multiplicity and playfulness of the third wave. It is also a call to action for new voices to redefine a feminism that is not only personally aware, but also politically involved. (source: Nielsen Book Data)
Section: x, 338 p. ; 24 cm Table des matières Introduction / Rory Dicker and Alison Piepmeier The "big lie": false feminist death syndrome, profit, and the media / Jennifer L. Pozner In a word, Baywatch / Susannah B. Mintz. Reviving Lolita ; or, because junior high is still hell / Alyssa Harad "That's not fair!" : nurturing girls' natural feminism / Nancy Gruver Voices and visions : a mother and daughter discuss coming to feminism and being feminist / Roxanne Harde and Erin Harde Please–stop thinking about tomorrow : building a feminist movement on college campuses for today / Sarah Boonin Who's the next Gloria? : the quest for the third wave superleader / Jennifer Baumgardner and Amy Richards Buffy the vampire slayer : the next generation of television / Michele Byers Third World, third wave feminism(s) : the evolution of Arab American feminism / Susan Muaddi Darraj Feminism's family problem : feminist generations and the mother-daughter trope / Astrid Henry Do the ladies run this– ? Some thoughts on hip-hop feminism / Gwendolyn D. Pough The transfeminist manifesto / Emi Koyama Hearing the daughter voice : The Bat Kol as Rrrabbi Grrrl / Alana Suskin Rocking the gender order / Mimi Schippers Pranks and fake porn : doing feminism my way / Kristina Sheryl Wong Afterword / Katha Pollitt and Jennifer Baumgardner.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; féminisme pop; militance; premier cycle; périodes historiques; soc2014; thématiques; transféminisme; troisième vague